Cerita Rakyat Sentani Asal Usul Marga Ongge dan Relevansinya Sebagai Bahan Bacaan Anak: Folklore of Sentani Entitled Asal Usul Marga Ongge and its Relevance as Reading Material for Primary School Students - Normawati, Normawati (Balai Bahasa Provinsi Papua, 2023)
Sentani, in Jayapura Regency has many comparably living interesting folktales toward other places in Indonesia. Those folktales, however, have not yet been explored and exploited as children reading material, especially in primary school. Accordingly, this study discusses about presentation suitability of folktale entitled “Asal Usul Marga Ongge” toward intellectual development of children. Folktales as data sources were orally collected from informants. Researcher analyzes this study using descriptive qualitative method. The result shows that story is suitable as reading material for children 11 years old and above. This is shown by the usage of developing or complicated character with social and culture background of Sentani people. Message or character value is complicated either, especially for primary school students period. The story tells us about, political knowledge and sensible nature that should be owned by tribe leader, or Ondofolo, and his descendant. The message includes character value as a person and as a society member. The value as person including honesty and hard-work. As a member of a society, on the other hand, including (a) realizing of self-right and self-obligatory and other people as well, (b) obeying any social rules.